Finite Difference Method for Two-Dimensional Fractional Partial Differential Equation with parameter - Gorial, I. I. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, we introduce and discuss an algorithm for the numerical solution of two- dimensional fractional partial differential equation with parameter. The algorithm for the numerical solution of this equation is based on implicit and an explicit difference method. Finally, numerical example is provided to illustrate that the numerical method for solving this equation is an effective solution method.